(untitled) (Communications in Mathematical Research, 2019)
A class of nonlinear fractional differential equations with conformable fractional differential derivatives is studied. Firstly, Green's function and its properties are given. Secondly, some new existence and multiplicity conditions of positive solutions are obtained by the use of Leggett-Williams fixed-point theorems on cone.